2013
DOI: 10.4066/amj.2013.1730
|View full text |Cite
|
Sign up to set email alerts
|

Predicting ICU admissions from attempted suicide presentations at an Emergency Department in Central Queensland

Abstract: We identified drug overdose as a strong predictor of ICU admission, while age, drug overdose and history of previous suicide attempts predict hospital admission. We recommend reviewing physician practices, especially safe medication, in suicide risk patients. Our study also highlights the need for continued close collaboration by acute care and community mental health providers for quality improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
5
0
2
Order By: Relevance
“…Due to lack of data from the sources, it was a challenge to identify the motivating factors for choosing OD over NOD methods. However, the near significant gender difference in suicide methods observed in our results, mirrored evidence in the literature that women tend to use less violent suicide methods like poisoning [20, 21] as compared to men who tend to use NOD methods such as hanging [22]. …”
Section: Discussionsupporting
confidence: 86%
“…Due to lack of data from the sources, it was a challenge to identify the motivating factors for choosing OD over NOD methods. However, the near significant gender difference in suicide methods observed in our results, mirrored evidence in the literature that women tend to use less violent suicide methods like poisoning [20, 21] as compared to men who tend to use NOD methods such as hanging [22]. …”
Section: Discussionsupporting
confidence: 86%
“…In this study, drug overdose was the most common method of suicide (52.4% of the total patients), and had similar rates in both the hospitalised and discharged groups. Walker et al had reported drug overdose to be a strong predictor of ICU admission [25] while Kim et al classi ed stabbing, hanging, drowning, and jumping off a height as clinically serious, lethal methods, and severe depression, psychological disturbance, and repetitive suicidal ideation as factors that indicated high medical severity [26]. This study excluded patients who died while in the ED or within 24 h of hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, drug overdose was the commonest method of suicide (52.4% of the total patients), and had similar rates in the hospitalization and discharge groups. Walker et al had reported drug overdose to be a strong predictor of ICU admission [18] | Kim et al classi ed stabbing, hanging, drowning, and jumping off a height as clinically serious, lethal methods, and severe depression, psychological disturbance, and repetitive suicidal ideation as factors that indicated high medical severity [19]. This study excluded patients who died while in the ED or within 24 h of hospitalization, and those patients who represented less than 10% of all suicide attempters.…”
Section: Discussionmentioning
confidence: 99%